Student Perception of Learning Versus Performance in Project Management Education - Wilson, Shellyanne (Journal of Management and Business Education, 2022)
This study investigates student perception of learning versus student performance in a project management undergraduate course. Student perception of project management learning is examined using a retrospective survey of 147 students from two academic years. The students’ performance is measured by their final grade. Data are analysed using Wilcoxon signed rank and Chi-square tests. The results show students reported increased perceived knowledge of all project management process groups, where the lowest and highest mean increases were Executing and Initiating respectively. The results, however, show there were no significant relationships between students’ perception of learning and student performance. The students’ perception results, however, can inform teaching strategies regarding where emphasis maybe needed in the process groups with the lowest perceived mean scores.